A Commercial Low Cost, Highly Efficient UC3842 based High Brightness LED (HBLED) Lamp - Devi Maheswaran; Sreedevi V T (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
The conventional lighting sources like incandescent and fluorescent lamps are replaced by High Brightness Light Emitting Diodes (HB-LEDs). In this paper, a HBLED driver using a Single Ended Primary Inductor Converter (SEPIC) with input Power Factor Correction (PFC) is presented.  PFC is accomplished using a commercial inexpensive Peak Current Mode Controller (PCMC) IC UC3842 is newly combined with SEPIC converter. Extensive simulation results are carried out and a laboratory prototype to power 18W LED array from AC mains is implemented and the results are presented in detail.